PENDIDIKAN EKSISTENSIALISME DAN PENGUATAN KEBEBASAN INDIVIDU DALAM PEMBELAJARAN DI ERA DIGITAL - Ainil Mahbubah; Alfiatur Rahmah; Zuhairina, Ikrima Aulia; Muhlisin, Muhlisin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has brought significant changes to the world of education, including how students acquire information, interact, and build understanding. Amid these changes, a challenge has emerged to ensure that individual freedom remains an essential part of the learning process. This study aims to examine the relevance of existentialism in education and analyze its contribution to strengthening individual freedom in learning in the digital age. The study employs a literature review (library research) using a descriptive qualitative approach. Data were obtained from various scientific journals, academic books, and relevant literature discussing existentialism, education, freedom of learning, and digital learning. Analysis was conducted through data reduction, thematic data presentation, and critical synthesis of the selected sources. The results of the study indicate that existentialism positions learners as free, authentic individuals who are responsible for their choices and learning processes. The values of freedom, responsibility, and the search for meaningwhich lie at the core of existentialismhave proven relevant for addressing various challenges in digital learning, such as technological dependence, identity crises, and the influence of algorithms that have the potential to limit independent thinking.Furthermore, learning approaches that provide space for reflection and decisionmaking.